Percent Pulmonary Damage on Hospital Admission is Predictive of COVID-19 Aggravation, but Serum Protein Electrophoresis is Not - Stéphane Di Mascio; Fadi Khadra; Christine Tchikladzé-Mérand; Sandrine Labroy; Mélanie Decambron (Journal of Global Infectious Diseases)
Introduction: Electrophoresis of serum proteins (ESP) reveals the proteins present during the acute phase of a disease and enables the detection and monitoring of inflammatory syndrome. The aim of this study was to explore whether ESP could help to identify patients at risk of COVID-19 aggravation. Methods: This was a two-center, observational, prospective study carried out between March 2021 and February 2022. Patients hospitalized in a COVID-19 unit, with an oxygen requirement of <6 L/min, were included. ESP was carried out every 4 days until clinical aggravation or discharge. Aggravation was defined by the requirement for >6 L/min oxygen, intensive care unit admission, or death. Risk factors for aggravation evaluated included age, comorbidities, serum proteins (albumin, globulins), % pulmonary damage (%PD) on computed tomography scans, D-dimers, C-reactive protein (CRP), ferritin, lymphocytes, and PO2. Student’s t-test or Wilcoxon–Mann–Whitney test (quantitative variables) and Chi-square or Fisher’s test (qualitative variables) were used for univariate analysis. Risk factors for COVID-19 aggravation were analyzed by logistic regression. The threshold of significance was 5%. Results: A total of 161 patients were analyzed (mean [±standard deviation (SD)] age: 67.3 ± 16.6 years; 50.9% female). COVID-19 aggravated in 37 patients, within a mean (±SD) of 4.1 ± 2.6 days. In univariate analysis, α-1 globulins (P = 0.04), %PD (P = 0.02), and CRP (P = 0.02) at inclusion were significantly higher in patients whose disease aggravated. In multivariate analysis, %PD at inclusion was the only factor significantly linked to aggravation (OR = 2.3 [95% CI: 1.3‒4.7]; P = 0.01). Conclusions: ESP was not predictive of clinical aggravation in hospitalized COVID-19 patients.